Defaunation effects on plant recruitment depend on size matching and size trade-offs in seed-dispersal networks. Issue 1855 (31st May 2017) - Donoso, Isabel; Schleuning, Matthias; García, Daniel; Fründ, Jochen
Abstract : Defaunation by humans causes a loss of large animals in many ecosystems globally. Recent work has emphasized the consequences of downsizing in animal communities for ecosystem functioning. However, no study so far has integrated network theory and life-history trade-offs to mechanistically evaluate the functional consequences of defaunation in plant–animal networks. Here, we simulated an avian seed-dispersal network and its derived ecosystem function seedling recruitment to assess the relative importance of different size-related mechanisms. Specifically, we considered size matching (between bird size and seed size) and size trade-offs, which are driven by differences in plant or animal species abundance (negative size–quantity relationship) as well as in recruitment probability and disperser quality (positive size–quality relationship). Defaunation led to impoverished seedling communities in terms of diversity and seed size, but only if models accounted for size matching. In addition, size trade-off in plants, in concert with size matching, provoked rapid decays in seedling abundance in response to defaunation. These results underscore a disproportional importance of large animals for ecosystem functions. Downsizing in ecological networks will have severe consequences for ecosystem functioning, especially in interaction networks that are structured by size matching between plants and animals.